Eruptive syringoma: a case report - Saikia, Siddhartha S.; Jagati, Ashish G.; Rathod, Santoshdev P.; Chaudhary, Raju G. (International Journal of Research in Dermatology, 2019)
Eruptive syringoma is a rare clinical presentation of a benign tumor of the eccrine ducts. Its usual presentation is small, smooth, skin coloured papules with flattened or rounded tops on the anterior body surfaces including face. It usually affects adult female. Treatment of this benign condition is cosmetic only. Herein, we report an uncommon presentation in a 30 years old female who presented with multiple, asymptomatic, skin coloured papules over face, neck, chest and thighs. Histopathology showed collection of cystic ducts and epithelial cords with comma like tails in dermis confirming a diagnosis of eruptive syringomas.